PENERAPAN PEMBELAJARAN DIGITAL MENGGUNAKAN MEDIA DALAM TEKNOLOGI PENDIDIKAN PADA ERA SOCIETY 5.0 DI SEKOLAH DAN PERGURUAN TINGGI: PENERAPAN PEMBELAJARAN DIGITAL MENGGUNAKAN MEDIA DALAM TEKNOLOGI PENDIDIKAN PADA ERA SOCIETY 5.0 DI SEKOLAH DAN PERGURUAN TINGGI - Frezy Paputungan; Imam Mashudi (Jurnal Ilmu Pendidikan dan Budaya, 2022)
Most countries in the world are currently facing the 4.0 industrial revolution, including our beloved country, Indonesia. The industrial revolution 4.0 is an innovation that uses or fully implements information and communication technology. Or it can be said as robotization technology. Artificial intelligence and the internet have largely replaced the role of humans. So that from this industrial revolution raises concerns about the role of humans in life. Because of this, the industrial revolution 5.0 or better known as Society 5.0 emerged. Society5.0 is an innovation in the world of technology that aims to solve problems that arose in the industrial era 4.0. Technology continues to grow rapidly, including robotics applications which are feared to reduce the role of humans. So through Society 5.0 it is hoped that the role of humans will increase or maximize Human Resources (HR). So that it can overcome and anticipate the global trends that appear in industry 4.0. Society 5.0 is an era where digital technology is applied to human life. The country that first implemented Society 5.0 was Japan. The background of the 5.0 industrial revolution, there is a fear of reducing or decreasing the role of human resources (HR), because the application of robotics is growing rapidly. According to the Cabinet Office of Japan, Society5.0 is defined as a human-centered society, which balances economic progress with solving social problems through a system that highly integrates cyberspace and physical space.